Early-Pregnancy Metabolic Syndrome and Subsequent Incidence in Gestational Diabetes Mellitus in Arab Women - Wani, Kaiser; Sabico, Shaun; Alnaami, Abdullah M.; Al-Musharaf, Sara; Fouda, Mona A.; Turkestani, Iqbal Z.; Al-Ajlan, Abdulrahman; Alshingetti, Naemah M.; Alokail, Majed S.; Al-Daghri, Nasser M. (Frontiers in Endocrinology, 2020)
Introduction: This study aimed to investigate the association between components of metabolic syndrome (MetS) at first trimester and development of Gestational diabetes mellitus (GDM) in 498 Saudi pregnant women. Materials and Methods: Biochemical and anthropometric parameters were determined at the first trimester and MetS components were defined. Participants were screened for GDM at follow up according to International Association of Diabetes and Pregnancy Study Group (IADPSG) criteria. The main outcome measures were development of GDM and GDM risk versus MetS components at first trimester. Results: One hundred twenty three (24.7%) were diagnosed with GDM according to IADPSG criteria. GDM risk was significantly higher for participants with hypertriglyceridemia at 1st trimester even after adjusting for age, BMI and parity (OR: 1.82; CI: 1.1–3.7, p=0.04). Furthermore, the odds of hyperglycemia at 1st trimester was significantly higher in GDM than in non-GDM participants even after adjustments (OR: 2.13, 95% CI: 1.1 to 4.3, p=0.038). The receiver operating characteristic (ROC) for predicting GDM revealed an area under the curve (AUC) of 0.69 (95% CI: 0.64 to 0.74, p<0.001) and 0.71 (95% CI: 0.65 to 0.77, p<0.001) for first-trimester hyperglycemia and hypertriglyceridemia respectively. Conclusions: The incidence of GDM in Saudi pregnant women was strongly associated with hyperglycemia and hypertriglyceridemia at first trimester. These findings are of clinical importance, as an assessment of MetS in early pregnancy can identify women at higher risk of developing GDM.